SOLUTION TO STUNTING PREVENTION THROUGH PREMARITAL COUNSELING: A MAṢLAḤAH-BASED APPROACH IN KAMPUNG RAKYAT, LABUHANBATU SELATAN - Kasanova, Aldi; Firmansyah, Heri (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2024)
This study investigates the implementation of premarital counseling for engaged couples as a preventive measure against stunting from the perspective of maslahah (public interest). The research focuses on the efforts made by the Office of Religious Affairs (KUA) in Kampung Rakyat Subdistrict, Labuhanbatu Selatan Regency, in educating future spouses about stunting prevention. The research employs a qualitative approach, using a case study method to analyze the various strategies implemented by KUA in identifying, preventing, and addressing stunting cases among children in the region. Data were collected through interviews, observations, and document analysis to capture the role of KUA and its collaboration with health agencies. The findings highlight the pivotal role of KUA in providing essential education and guidance to prospective couples on stunting prevention. The strategies include offering premarital counseling, disseminating health information, and fostering partnerships with relevant health sectors to ensure adherence to applicable laws and regulations. The study also explores the positive outcomes and challenges of these initiatives in Desa Tanjung Medan, Kampung Rakyat. This research is novel in its integration of the maslahah principle into the evaluation of stunting prevention efforts within premarital counseling, offering a unique Islamic legal perspective on addressing public health concerns through religious guidance. The study suggests that strengthening KUA's role in stunting prevention through collaborative efforts with healthcare institutions can significantly enhance the effectiveness of premarital counseling programs. It also underscores the importance of aligning religious and public health initiatives to ensure better outcomes for future generations.